A Visual Hermeneutics Study of Political Ads in Governor Election Campaigns on Instagram - Paris, Atika Salman; Nuruddin, Nuruddin; Hasanah, Nurlaila; Suryadi, Hendra (LPPM Institut Pendidikan Nusantara Global, 2024)
The increasing use of social media, particularly Instagram, as a primary platform for political campaigns demands an in-depth understanding of how visual elements influence public perception. This study addresses two main research problems: first, what meanings are embedded in the images of gubernatorial political advertisements on Instagram? Second, how can a hermeneutic approach uncover the visual dimensions within such campaigns? The purpose of this study is to analyze the visual messages in gubernatorial political campaigns on Instagram and understand the contextualization and visual interpretation of political advertisements using a hermeneutic approach. Using a qualitative method based on visual hermeneutics, data in the form of political advertisement images were analyzed through visual mapping and semantic interpretation. The results show that campaign advertisements featuring the gubernatorial candidate alongside the music group Slank successfully built a connection between the candidate and strong social and cultural identities, particularly among young voters. Visual elements such as facial expressions, color schemes, and image composition reinforced the political message and created an image of the candidate as a progressive figure closely connected to the community. Hermeneutic analysis further revealed that these advertisements not only conveyed political messages but also constructed cultural narratives linking the candidate to values of change and solidarity. This study contributes to enriching the understanding of the role of visual elements in political campaigns on social media and demonstrates how these elements can be strategically utilized to shape public perception, enhance the candidate's image, and influence voter preferences in an increasingly digital and visual electoral context.